TNFα polymorphisms and risk of psoriatic arthritis. Issue 7 (10th November 2005) - Rahman, P; Siannis, F; Butt, C; Farewell, V; Peddle, L; Pellett, F; Gladman, D
Abstract : Background: Tumour necrosis factor α (TNFα) is a cytokine of critical importance in psoriatic arthritis. Objectives: (1) To examine the association between TNFα promoter gene polymorphisms and psoriatic arthritis in two well characterised Canadian populations with the disease; (2) to carry out a meta-analysis of all TNFα association studies in white psoriatic arthritis populations. Methods: DNA samples were genotyped for five TNF variants by time of flight mass spectrometry using the Sequenom platform. All five single nucleotide polymorphisms were in the 5′ flanking region of TNFα gene at the following positions: −1031 (T→C), −863 (C→A), −857 (C→T), −308 (G→A), and −238 (G→A). Primary analyses were based on logistic regression. Summary estimates of disease/genotype relations from several studies were derived from random effects meta-analyses. Results: 237 psoriatic arthritis subjects and 103 controls from Newfoundland and 203 psoriatic arthritis subjects and 101 controls from Toronto were studied. A combined analysis of data from both populations, showed a significant association between disease status and the −238(A) variant (p = 0.01). The meta-analysis estimate for the −238(A) TNFα variant in eight psoriatic arthritis populations was also significant (odds ratio = 2.29 (95% confidence interval, 1.48 to 3.55)). Conclusions: Analysis of TNFα variants in psoriatic arthritis populations shows that the −238 (A) variant is a significant risk factor for this disease.